An investigation of the concept Religious Communication - Ansie Slabbert (Communicare)
This paper is based on a study to investigate the complex and diverse concept of religious communication. This paper is based on a study to investigate the complex and diverse concept of religious communication. In this study the construct, religious communication, is demarcated and defined by using a comparison between two forms of religion: Protestantism as found in the three Sisters Churches in South Africa and the New Age movement. The religious communications pro cess is analysed through the symbolic interactionist perspective as a broad theoretical point of departure and within it a religious communication model was developed. In the study the religious communication process is defined within the parameters of the individual and his different relationships (with God/ godhead, fellow-man and himself), his symbolic interaction and social context within which the religious communication takes place The conclusion was reached that religious communication is more than Just intra-, Inter-, or spiritual/Intuitive communications. It is a true and real communication action that takes place on a two-dimensional level Since the study is based on a qualitative investigation there is room for the model to be empirically tested in possible future research